Alternative classification diagrams for AGN-starburst galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Aydar, Catarina P.; Steiner, J. E.; Dors, Oli
Abstract: The aim of diagnostic diagrams is to classify galactic nuclei according to their photoionizing source using emission-line ratios, differentiating starburst regions from active galactic nuclei (AGN). However, the three traditional diagnostic diagrams can sometimes be ambiguous with regard to a single object. The main goal of the present work is to propose alternative diagnostic diagrams by using distinct combinations of emission lines ratios. We present these diagrams using data from the Sloan Digital Sky Survey. With these new diagrams, it is possible to better distinguish the ionizing source in nuclei of galaxies and also to study the parameters that are relevant when considering both kinds of objects, starbursts and AGN.